The scramble for Africa's oil: a blessing or a curse for African states? - Tipchanta, Deekana (2012)
This thesis analyses foreign intervention in oil-rich African states which have contributed to the resource curse problem in the latter. It concentrates on the role of former colonial powers-France and Britain-as well as new players-the United States, China and multinational agencies who have deployed policies and carried out practices in securing Africa’s oil resources.